Morphological features of the umbilical cord in equine (Equus caballus, Linnaeus, 1758) - Carvalho, Fernando de Sales Resende; Miglino, Maria Angélica; Severino, Renato Souto; Ferreira, Fernando Antonio; Santos, Tatiana Carlesso dos (Brazilian Journal of Veterinary Research and Animal Science, 2001)
The disposition and ramification of the arteries and veins of the umbilical cord from cross-bred equine in different pregnancy stages were studied. Thirty fetuses, 18 male and 12 female with age varying from 73 to 249 days, were used and the umbilical vessels were injected with Neoprene latex 650 colored solution and further dissected. The length of the umbilical cord varied from 28 to 70 centimeters (mean of 47.5 centimeters). The umbilical cord included the urachus, two arteries and one umbilical vein. This latter presented, in average, 20.5 cm in length, and was constituted of two (86.66%) or three (13.33%) tributary veins. Arteriovenous anastomoses, funicular vessels besides the vasa vasorum were also observed. Arteriovenous anastomoses were found in 83.33% of the cases, varying from one to eight, and presented the following disposition: transversal (57.14%), convergent (9.52%), oblique (28.57%), "H"-shaped (2.38%), "V" transversal (1.19%) and "X" transversal (1.19%).